A Rehabilitation Program for Correcting Lateral Deviation Resulting from Lumbar Disc Injuries in Young Wrestlers - Mahmood, Salah (Journal of Physical Education, 2025)
Lumbar disc injuries are among the most common issues affecting young wrestlers, often leading to functional disorders of the spine, notably lateral deviation, which negatively impacts motor performance and physical balance. This study aims to design a rehabilitation program based on specialized therapeutic exercises intended to correct lateral deviation, enhance spinal efficiency, and reduce associated pain. The research was conducted on a sample of young wrestlers suffering from lumbar disc herniation accompanied by lateral deviation, who underwent a structured rehabilitation program over a specific period that included core strengthening exercises, balance improvement drills, and stretching and relaxation activities. The effectiveness of the program was evaluated through pre- and post-intervention measurements, assessing deviation angle, pain intensity, and physical performance level. The results revealed a marked improvement in the correction of lateral deviation, a reduction in pain levels, and an enhancement in physical performance, confirming the efficiency of the rehabilitation program in promoting spinal function and mitigating the effects of lumbar disc injuries. The study recommends adopting such programs within therapeutic plans for injured wrestlers to ensure their safe and rapid return to competitive sports.